1999
DOI: 10.1183/09031936.99.13353599
|View full text |Cite
|
Sign up to set email alerts
|

Pathological and radiological changes in resected lung specimens in Mycobacterium avium intracellulare complex disease

Abstract: The present study was designed to evaluate the pathological and immunohistochemical findings of Mycobacterium avium intracellulare complex (MAC) lung infection.A retrospective study was performed in five cases with positive cultures for MAC in whom lung resections were performed between January 1989 and December 1996. A determination of whether or not MAC caused pulmonary disease was made using the 1997 criteria defined by the American Thoracic Society. In addition, MAC was cultured from all of the five lung s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
80
0
5

Year Published

2002
2002
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 115 publications
(86 citation statements)
references
References 12 publications
1
80
0
5
Order By: Relevance
“…Immunohistochemistry showed massive infiltration, mostly by macrophages and T cells, which are the characteristic cellular components of granulomas after mycobacterial infection (26,27). We observed a distinct pattern of distribution of macrophages, T cells, and B cells in which a central region of macrophages is interspersed with T cells and the next layer of granulomatous material contains aggregates of T and B cells (27).…”
Section: Discussionmentioning
confidence: 84%
“…Immunohistochemistry showed massive infiltration, mostly by macrophages and T cells, which are the characteristic cellular components of granulomas after mycobacterial infection (26,27). We observed a distinct pattern of distribution of macrophages, T cells, and B cells in which a central region of macrophages is interspersed with T cells and the next layer of granulomatous material contains aggregates of T and B cells (27).…”
Section: Discussionmentioning
confidence: 84%
“…Pul- (1,10,13). In a previous report, we demonstrated pathological findings of MAC infection (9). Our present study also examined the appearance and distribution of myofibroblasts.…”
Section: Discussionmentioning
confidence: 94%
“…Moreover, all patients in the MAC-culture positive group had findings of small nodules on CCT. Some careful investigation of CCT and histological findings revealed that small nodular lesions were caused by granulomas formed as a specific response to mycobacterial infection [13,14]. Furthermore, the individuals with MAC colonisation, who had a single and small amount of culturepositive MAC but did not have clinical symptoms or abnormal lesions on CCT findings, were excluded from the present study at enrolment.…”
Section: Discussionmentioning
confidence: 99%